Corin deficiency impairs cardiac function in mouse models of heart failure - Niu, Yayan; Zhou, Tiantian; Zhang, Shengnan; Li, Wenguo; Wang, Kun; Dong, Ningzheng; Wu, Qingyu (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Corin is a protease in the natriuretic peptide system. Deleterious CORIN variants are associated with hypertension and heart disease. It remains unclear if and to what extent corin deficiency may contribute to heart failure (HF). Methods: Corin knockout (KO) mice were used as a model. Cardiac function was assessed by echocardiography and tissue analysis in Corin KO mice at different ages or subjected to transverse aortic constriction (TAC), which increased pressure overload. Heart and lung tissues were analyzed for cardiac hypertrophy and lung edema using wheat germ agglutinin, Sirius red, Masson's trichrome, and Prussian blue staining. Recombinant corin was tested for its effect on cardiac function in the TAC-operated Corin KO mice. Selected gene expression in the heart was examined by RT-PCR. ELISA was used to analyze factors in plasma. Results: Corin KO mice had progressive cardiac dysfunction with cardiac hypertrophy and fibrosis after 9 months of age, likely due to chronic hypertension. When Corin KO mice were subjected to TAC at 10-12 weeks of age, cardiac function decreased more rapidly than in similarly treated wild-type mice. When the TAC-operated Corin KO mice were treated with recombinant corin protein, cardiac dysfunction, hypertrophy, and fibrosis were ameliorated. The corin treatment also decreased the gene expression associated with cardiac hypertrophy and fibrosis, increased plasma cGMP levels, lowered plasma levels of N-terminal pro-atrial natriuretic peptide, angiotensin, and aldosterone, and lessened lung edema in the Corin KO mice subjected to TAC. Conclusion: Corin deficiency impairs cardiac function and exacerbates HF development in mice. Corin protein may be used to reduce cardiac hypertrophy and fibrosis, suppress the renin-angiotensin-aldosterone system, and improve cardiac function in HF.